Analysis of professional collaboration between community health nurses and environmental health officers in Malawi - Kafwe, Fabian K.; Tembo, Charles; Nyasulu, Yohane M. Z.; Kalua (Unisa Press, 2022)
A study was done in Malawi with the aim of analysing and clarifying dimensions of collaboration between Environmental Health Officers (EHO) and Community Health Nurses (CHN's). The objectives of the study were to identify the nature and level of collaboration between EHO's and CHN's; to identify possible reasons for collaboration or non-collaboration and to explore perceptions about collaboration between the two professional groups.